Resolving "too big to fail" - Nicola Cetorelli; James Traina (Federal Reserve Bank of New York, 2018)
Using a synthetic control research design, we find that "living will" regulation increases a bank's annual cost of capital by 22 basis points, or 10 percent of total funding costs. This effect is stronger in banks that were measured as systemically important before the regulation's announcement. We interpret our findings as a reduction in "too big to fail" subsidies. The size of this effect is large: a back-of-the-envelope calculation implies a subsidy reduction of 42 billion annually. The impact on equity costs drives the main effect. The impact on deposit costs is statistically indistinguishable from zero, representing a good placebo test for our empirical strategy.
Keywords: G21; G28; 330; cost of capital; time consistency; too big to fail; resolution plans; Dodd-Frank